2018
DOI: 10.1007/s00018-018-2760-9
|View full text |Cite
|
Sign up to set email alerts
|

Lnc-ing non-coding RNAs with metabolism and diabetes: roles of lncRNAs

Abstract: Type 2 diabetes is a complex metabolic disorder characterized by insulin resistance and pancreatic β-cell dysfunction. Deregulated glucose and lipid metabolism are the primary underlying manifestations associated with this disease and its complications. Long non-coding RNAs (lncRNAs) are a novel class of functional RNAs that regulate a variety of biological processes by a diverse interplay of mechanisms including recruitment of epigenetic modifiers, transcriptional and post-transcriptional regulation, control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 112 publications
1
55
0
Order By: Relevance
“…More important, the distinct influence on the biology of vascular cells conferred by lncRNAs has been associated with diabetic vascular complications (Leung, Amaram, & Natarajan, ). A previous study indicated that lncRNAs could serve as biomarkers or therapeutic targets in the treatment of DM and its related complications (Goyal, Kesharwani, & Datta, ). In addition, research has indicated there to be a correlation between highly expressed lncRNA H19 and a host of human cancers, including multiple myeloma, and plays a significant role in the occurrence of cancers (Pan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…More important, the distinct influence on the biology of vascular cells conferred by lncRNAs has been associated with diabetic vascular complications (Leung, Amaram, & Natarajan, ). A previous study indicated that lncRNAs could serve as biomarkers or therapeutic targets in the treatment of DM and its related complications (Goyal, Kesharwani, & Datta, ). In addition, research has indicated there to be a correlation between highly expressed lncRNA H19 and a host of human cancers, including multiple myeloma, and plays a significant role in the occurrence of cancers (Pan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The differential expression of the selected lncRNAs in vivo reconfirmed the results from the gene array analysis. LncRNAs have been reported to be involved in the process of diabetes development ; our newly discovered lncRNAs may provide new candidates for T2DM study.…”
Section: Introductionmentioning
confidence: 94%
“…In the survey, Roggli et al (2012) investigated the effects of miRNAs on the PBCs dysfunction in NOD animals. They observed that the levels of miR-29a, miR-29b, and miR-29c increased in pancreas islets of NOD animals thru the prediabetic phases and also in the human islets (Goyal et al, 2018). It has been revealed that lncRNAs' effects on gene expression procedure can be performed at the each stage of the transcription, posttranscription and translation.…”
Section: Oxidative Stress and T2dmentioning
confidence: 99%
“…A small portion of these long noncoding RNAs (lncRNAs) have shown to regulate gene expression by some procedures, such as modulation of chromosomal structure, transcription, mRNA transport or translation (St. Laurent, Wahlestedt, & Kapranov, ). Some of the recent investigations have discovered many lncRNAs in β cells of the human Langerhans islets (Goyal, Kesharwani, & Datta, ; Morán et al, ; You et al, ). It has been suggested that β‐cell lncRNAs controlled extracellular concentrations of glucose.…”
Section: Introductionmentioning
confidence: 99%